Influence of host-specific and locally isolated multi-strain probiotics on piglet performance, mortality, inflammatory response, and gut microbiome - Katatikarn Sahatsanon; Panneepa Sivapirunthep; Korawan Sringarm; Chaiwat Arjin; Patipan Hnokaew; Kamon Chaweewan; Chanporn Chaosap (My University, 2024)
Objective: This study aimed to assess the impact of host-specific and locally isolated multistrain probiotics on piglet performance, mortality, inflammatory responses, and gut microbiome.Methods: A total of 52 piglet litters-34 from Landrace sows and 18 from Large White sows-were allocated to two groups: a control group and a multi-strain probiotic group. The probiotic group comprised seven strains of lactic acid bacteria (MLAB): Lactobacillus brevis, Lactobacillus reuteri, Lactobacillus paraplantarum, Lactococcus lactis, Lactobacillus pentosus, Weissella cibaria, and Pediococcus pentosaceus. Each strain was included in equal concentrations, resulting in a final liquid mixture containing 109 colony forming units/mL. The MLAB group received the probiotics orally starting from 7 days of age until weaning at four weeks. Following weaning, supplementation continued via feed spraying for an additional four weeks.Results: MLAB supplementation did not significantly affect piglet performance but showed a trend towards reducing the mortality rate (p = 0.06). It influenced the inflammatory response by upregulating the expression of anti-inflammatory cytokines interleukin (IL)-4 and IL-10 (p<0.05). Microbial community analysis indicated that MLAB supplementation increased both microbial diversity (Simpson index: p = 0.06) and species richness (Chao1 index: p = 0.02). Piglets receiving MLAB had a significantly higher abundance of the phylum Firmicutes (p<0.01) compared to the control group, while the abundance of the phylum Bacteroidota was markedly reduced (p<0.01). In addition, the relative abundance of the bacterial genera Prevotellaceae_NK3B31 (p<0.01) and Chlamydia (p = 0.03) was lower in the MLAB group.Conclusion: Overall, these results suggest that while MLAB supplementation does not directly improve piglet growth performance, it has the potential to improve immune function and promote a healthier gut microbiota in weaning piglets, which could ultimately reduce mortality rates.
Keywords: Strain (injury); Host response; Inflammatory response; Gut microbiome; Gut microbiota and health